Survei Tingkat Kebugaran Jasmani Siswa Kelas V Dan VI SD Negeri Sidomulyo 2 Kecamatan Wates Kabupaten Kediri Tahun Ajaran 2022/2023 - Muhamad Yakup Wilji Sando; M. Anis Zawawi; Wing Prasetya Kurniawan (YLPK Mahardhika, 2023)
This research is motivated by the importance of monitoring physical fitness in elementary school students. The results of an interview with the PJOK teacher at SD Negeri Sidomulyo 2 said that they had never conducted a physical fitness test on students. The purpose of this study was to determine the physical fitness level of fifth and sixth-grade students at Sidomulyo 2 Public Elementary School, Wates District, Kediri Regency for the 2022/2023 Academic Year. This research is quantitative descriptive research with a survey method. The sample for this study was all students in grades V and VI of Sidomulyo 2 Public Elementary School, Wates District, Kediri Regency for the 2022/2023 Academic Year using a total sampling technique. The research instrument used TKSI Phase C SD/MI including tests: Child Ball, Tot Tok Ball, Shuttle Run 4x10m Get Ball, Move The Ball, and Run 600 Meters. The results of the study showed that there were 2 students in the Very Good category with a percentage (of 4.44%), in the Good category there were 8 students with a percentage (of 17.78%), in the Moderate category there were 22 students with a percentage (48.89%), in the Less category as many as 13 students with a percentage (28.89%), and the Less Once category as many as 0 students with a percentage (0%). So it can be concluded that the level of physical fitness is in the